Effect of Peer Education on Knowledge of Human Papilloma Virus and Cervical Cancer among Female Adolescent Students in Benin City, Nigeria - Ayebo Evawere Sadoh; Chukwunwendu Okonkwobo; Damian Uchechukwu Nwaneri; Bamidele Charity Ogboghodo; Charles Eregiea; Osawaru Oviawe; Omolara Famuyiwa (Ubiquity Press, 2018)
Introduction: It is well documented that Human Papilloma Virus (HPV) is the cause of cervical cancer which is a major cause of morbidity and mortality especially in low- and middle-income countries. Vaccines against HPV are available. In developed countries where the vaccines have been deployed, lack of information among the target population (adolescents) is a major contributor to suboptimal uptake. In Nigeria, the vaccine is yet to be provided in the national programme on immunization, which is free, but it is available for a fee. In this study we determined the effect of peer education on the knowledge of female adolescents about HPV, cervical cancer, its treatment and prevention. Methods: This was an intervention study. The knowledge and awareness of female students of four secondary schools were assessed using a pre-tested self-administered questionnaire prior to the training of some of the students (peers). The trained students delivered messages on cervical cancer and HPV using fliers containing key information (peer training) to their school mates in formal delivery in a class setting. The knowledge and awareness of students, post-peer training, was then assessed. Results: There were 1337 students who responded to the baseline questionnaire while 1201 responded to the post-peer training questionnaire. Awareness of cervical cancer, knowledge of risk factors and cause of cervical cancer was low prior to the peer training. There was statistically significant improvement in awareness about cervical cancer and in the knowledge domains following peer training. Mean knowledge score prior to training was 12.94 ± 9.23 and this increased significantly to 53.74 ± 10.69 following peer training p < 0.0001. Conclusion: Peer training is effective in improving knowledge and awareness of secondary school students about HPV and cervical cancer.